Implementasi Jaringan VPN dengan Routing Protocol terhadap Jaringan Multiprotocol Label Switching (MPLS) - Fathurrahmad Fathurrahmad; Salman Yusuf (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2019)
The convergence of the internet and telecommunications is growing, with applications in it increasingly dependent on the availability of large bandwidth, with its QoS settings requiring networks and elements in them that provide full support for data security and increased network performance. The need for data transmission technology that not only facilitates routing and discovery of the best paths but can also provide security in data communication. This study discusses the implementation of VPN networks with routing protocols on the Multiprotocol Label Switching (MPLS) network. After implementation, MPLS network performance will be tested and compared to performance without MPLS using the model planned by the researcher. The specific purpose of this study is to show how routing protocols play an important role in strengthening data communication traffic management that supports MPLS capabilities of VPN networks and is applied to the AMIK Indonesia network architecture. This research will use the literature study method which is intended to obtain and study data contained in computers connected to networks in the AMIK Indonesia computer network laboratory. The conclusion obtained from this study is that MPLS VPN provides bandwidth efficiency in the backbone, MPLS VPN network applications have functioned functionally according to the initial plan of the study and the authors have also managed to configure different networks and obtain stable bandwidth.